Հայաստանի եվրասիական ընտրության քաղաքակրթական և քաղաքատնտեսական հիմքը - Բալասանյան Գրիգոր (YSU Journal of International Affairs, 2018)
The year 2013 was crucial for Armenia. It had two choices for development – either to act as some post-Soviet republics did and to sign the European Union Association Agreement, or taking into consideration the political, economic aspects of foreign policy and the problems of national security, to sign the agreement with Russia, Kazakhstan and Belarus in order to join the Customs union. Armenia chose the second way of development, as well as during the Armenian president’s visit to Russia, on 3 September 2013 it was announced that Armenia is going to join the Customs union. This decision divided the country into two unequal parts, the bigger of which accepted the president’s decision. It is an important point to be made that there are good prospects of the Eurasian integration for Armenia. The economy is rising and is getting more attractive for its neighbors. It means that it was a right decision to join the Eurasian economic union.